The Use of Dependencies for Improving the Precision of Program Static Analysis - M. I. Glukhikh; V. M. Itsykson; V. A. Tsesko (Моделирование и анализ информационных систем, 2011)
The development of dependency analysis methods in order to improve static code analysis precision is considered in this paper. Reasons for precision loss is abstract interpretation methods when detecting defects in program source code are explained. The need for program object dependency extraction and interpretation is justified by numerous real-world examples. A dependency classification is presented. The necessity for aggregate analysis of values and dependencies is considered. The dependency extraction from assignment statements is described. The dependency interpretation based on logic inference using logic and arithmetic rules is proposed. The methods proposed are implemented in defect detection tool Digitek Aegis and significant increase of precision is shown.